2018
DOI: 10.1016/j.molcel.2018.04.027
|View full text |Cite
|
Sign up to set email alerts
|

SHRED Is a Regulatory Cascade that Reprograms Ubr1 Substrate Specificity for Enhanced Protein Quality Control during Stress

Abstract: When faced with proteotoxic stress, cells mount adaptive responses to eliminate aberrant proteins. Adaptive responses increase the expression of protein folding and degradation factors to enhance the cellular quality control machinery. However, it is unclear whether and how this augmented machinery acquires new activities during stress. Here, we uncover a regulatory cascade in budding yeast that consists of the hydrophilin protein Roq1/Yjl144w, the HtrA-type protease Ynm3/Nma111, and the ubiquitin ligase Ubr1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 71 publications
4
55
0
Order By: Relevance
“…1 and 2 and SI Appendix, Fig. S2A) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Other studies, in the 1990s and afterward, have also identified many internal degrons, defined as degradation signals whose functionally essential elements do not include either Nt-residues or C-terminal (Ct) residues.…”
Section: Terminology For Proteolytic Pathways That Target N-termini Amentioning
confidence: 99%
See 3 more Smart Citations
“…1 and 2 and SI Appendix, Fig. S2A) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Other studies, in the 1990s and afterward, have also identified many internal degrons, defined as degradation signals whose functionally essential elements do not include either Nt-residues or C-terminal (Ct) residues.…”
Section: Terminology For Proteolytic Pathways That Target N-termini Amentioning
confidence: 99%
“…Pathway. A natural Ct-fragment of S. cerevisiae Roq1 acts as both a substrate and regulator of the Arg/N-degron pathway (41). Tunicamycin, a drug that causes protein misfolding in the endoplasmic reticulum (ER), increases the level of ROQ1 mRNA.…”
Section: Roq1 As a Substrate And Regulator Of The Arg/n-degronmentioning
confidence: 99%
See 2 more Smart Citations
“…N-degron (formerly termed "N-end rule") and C-degron (collectively referred to as "terminal degron") E3s recognize substrate N-or C-termini and regulate vast biology (Varshavsky, 2019). Nonetheless, beyond knowledge of pathways creating, exposing, or cloaking substrate N-or C-degrons, and structures showing their recognition by E3 ligases, there is limited structural information explaining regulation of terminal degron E3s (Brower et al, 2013;Choi et al, 2010;Dong et al, 2018;Hu et al, 2005;Koren et al, 2018;Lin et al, 2018;Matta-Camacho et al, 2010;Rao et al, 2001;Rusnac et al, 2018;Shemorry et al, 2013;Szoradi et al, 2018;Timms et al, 2019;Varshavsky, 2011;Wang et al, 2008). Moreover, Fbp1, Mdh2, and Icl1 each harbor natively exposed GID E3-targeting N-terminal prolines essential for their degradation (Hammerle et al, 1998).…”
Section: Introductionmentioning
confidence: 99%